RANCANG BANGUN ALAT CETAK SEAL APAR CHUBB 6 KG POWDER (Ã˜32.60 MM & Ã˜11.40 MM) MENGGUNAKAN SISTEM HIDROLIK (PENGUJIAN PERFORMA) - Muhammad, Novriadi; Arnoldi, Dwi; Arifin, Fatahul (Politeknik Negeri Sriwijaya, Indonesia, 2022)
In today's modern industry, there are many manufacturing machines of various types and different functions. A manufacturing machine is a tool that serves to facilitate the manufacture of components of an object. This study has a goal, namely to create an innovation in the world of mechanical engineering, especially in the field of compression molding with a hydraulic system using a bottle jack as the suppression system.The design of this seal press molding tool was designed and made by researchers in such a way with the aim that the tool can work optimally without failure. Testing on this tool is in the form of testing the performance of the jack with a pressure gauge installed and the production process which aims to determine the limits of the jack's ability in the production process in the hope of producing a perfect and precise o-ring seal.